Development of new localised formula basis for birthweight estimation: single variable and single constant coefficient based clinical formula - Kantharia, Preet S.; Patel, Rutwa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Introduction: The OBGY professionals’ primary goal is the well - being of fetal and mother. And, to achieve this, accurate fetal weight assessment is of prime importance. The prevalent fetal weight assessment formulas are of western origin and developed several decades ago, and hence its applicability throughout the world is always under debate. Methods: Present study of analytical formula basis development was carried out at the OBGY Department of a semi-urban cum rural tertiary care hospital, Dhiraj Hospital, SBKS MRC, at Gujarat. The study was undertaken over total of 50 pregnant women at full term pregnancy, till delivery. The actual localised birthweight data of these cases were collected and analysed, to derive a new formula basis and named as ‘SHF as singular kinematic’ (SSK). Same is verified, validated and compared using prevalent Johnson’s formula, for its significance, accuracy / error and positive predictive value. The Microsoft office, excel was used for the calculations and analysis and for graphs. Results: The new linear formula basis for birthweight estimation is BW(e-ssk)=(SFH-5.8)/8.588, is developed and got validated for its accuracy and predictive value. In comparison to prevalent clinical method Johnson and Toshach formula (JT), it was derived that new SSK formula has identical p value and higher PPV. Also, weighted average PPV % of the study using new SSK formula has resulted higher than, that of PPV % of Similar studies using prevalent formula. Conclusion: This study concludes that for clinical birthweight estimation, for pregnancy at term, using the newly derived formula basis “SFH as Singular Kinematic–SSK”, provides better accuracy for birthweight estimation over prevalent formula, while simultaneously solving the purpose of easy to learn and easy to use method for all concerned, even including non-medical persons and expecting mothers, at their own with basic training.